Experimental DCO-OFDM Optical Camera Communication Systems With a Commercial Smartphone Camera - Jenn-Kaie Lain; Zheng-Dao Yang; Ting-Wei Xu (IEEE Photonics Journal)
Modern handheld mobile devices are equipped with a complementary metal-oxide-semiconductor (CMOS) image sensor. These image sensors are capable of perceiving intensity changes in optically modulated signals, driving the rapid development of optical camera communication (OCC). In this study, direct-current offset orthogonal frequency division multiplexing (DCO-OFDM) was developed for a rolling shutter OCC system in order to improve the data transmission rates of OCC systems. Two DCO-OFDM OCC signal detection algorithms, namely the parabolic column vector selection (P-CVS) algorithm and the decomposition of extremely low frequency component (D-ELFC) algorithm, were proposed, along with a frequency-domain downsampling scheme, to eliminate the influence from both the blooming effect and shot noise. The experimental results, obtained after using a self-built DCO-OFDM OCC testbed with a general commercial smartphone camera, demonstrated that the D-ELFC algorithm outperformed in the bit error rate (BER) in comparison to the P-CVS algorithm and achieved a data transmission rate >22 kbps under the conditions of the BER being below the 20% forward error correction (FEC) limit and the illuminance being higher than 510 lux.